A case of myxedema coma precipitated by herpes zoster: a rare manifestation of a common disease - Chanda, Abhishek; Sonthalia, Nikhil; Hossain, Mohammad Saddam; Roy, Nirmalya; Sarkar, Suman; Bansal, Shikhar (International Journal of Advances in Medicine, 2022)
Myxedema coma is a disease state which is characterised by altered sensorium, hyponatremia, Bradycardia and hypotension. It is an emergency where prompt treatment is needed at the earliest, failure in identifying it is associated with fatal prognosis. The crisis is usually triggered by stressful events, the most common of which is infections like pneumonia and urinary tract infection. There has been sporadic case reports of myxedema coma associated with herpes zoster infection.